Vegetative Mitigation as an Alternative for Reducing Disaster Risk on The Calanimmur Coast, Pandeglang Regency, Indonesia - Kurniadi, Anwar (Technium Social Sciences Journal, 2022)
Structural mitigation at Carita beach, Labuan beach, Panimbang beach, and Sumur beach (Calanimmur) such as the installation of breakwaters, could not withstand the tidal waves and tsunami disaster. Therefore, it is necessary to apply mitigation in other ways that can withstand tidal waves of seawater and prevent the negative impact of the tsunami. This study aims to analyze the management of vegetative mitigation of mangrove forests on the Calanimmur coast, Pandeglang Regency to reduce disaster risk. The research method uses a qualitative method with a descriptive design that uses primary data from direct research in the field, and secondary to the results of previous studies, national journals, related books, and regulations related to mangrove forest mitigation, disaster risk reduction, and tsunami disasters. The results show that vegetative management of mangrove forest mitigation is expected to: 1) Carita beach, Labuan beach, and Panimbang beach can prevent or reduce tidal waves and tsunami so as not to directly damage the coast or land, and maintain tourism activities and aquaculture; 2) Sumur coast to prevent tidal waves and tsunamis from directly damaging the coast or land, and being developed as a pilot in Indonesia for combining new tourism and aquaculture. This study concludes that the development of physical mitigation as mangrove forest vegetation can reduce disaster risk such as preventing tidal waves and tsunami disasters from reaching the coast directly.